Distribution of interferon lambda‐3 gene polymorphisms in Australian patients with previously untreated genotype 1 chronic hepatitis C: Analysis from the PREDICT and CHARIOT studies. Issue 1 (January 2014) - Roberts, Stuart K; Mitchell, Joanne; Leung, Reynold; Booth, David; Bollipo, Steven; Ostapowicz, George; Sloss, Andrew; McCaughan, Geoffrey W; Dore, Gregory J; Thompson, Alexander; Crawford, Darrell HG; Sievert, William; et al.
Abstract Background and Aims The aim of this study was to examine the distribution of interferon lambda‐3 (IFN‐λ3) gene polymorphisms in previously untreated Australian patients with genotype 1 (Gt1) chronic hepatitis C (CHC) and to compare the IFN‐λ3 genotype frequency among the different ethnic populations. Methods This was a prospective, multicenter, observational study undertaken by the Australian Liver Association Clinical Research Network. Eligible subjects had Gt1 CHC and were being considered for and/or undergoing treatment. IFN‐λ3 single nucleotide polymorphisms were genotyped by the Applied Biosystems's Taqman single nucleotide polymorphism genotyping assay. Results Between May 2012 and June 2012, 1132 patients were recruited from 38 treatment clinics across Australia. Also, 561 subjects from the CHARIOT (collaborative group hepatitis C study using high dose Pegasys RBV Induction dose in genotype one) study of high‐dose interferon who had baseline serum available were retrospectively tested. The overall frequency of IFN‐λ3 rs12979860 CC/CT/TT genotypes was 36%, 52%, and 12%, and that of rs8099917 TT/TG/GG genotypes was 54%, 41%, and 5%, respectively. The prevalence of the favorable IFN‐λ3 rs12979860 CC and rs8099917 TT genotypes in Causcasians, Asians, Aboriginals, Maori/Pacific Islanders, and Mediterraneans was 32% and 52%, 80% and 86%, 33% and 63%, 77% and 88%, and 19% and 29%, respectively. Compared with Caucasians, the frequency of IFN‐λ3 CC was significantly higher among Asians (P < 0.0001) and Maori/Pacific Islander subjects (P < 0.0001). Conclusions The distribution of IFN‐λ3 polymorphisms among untreated patients with Gt1 CHC in Australia appears similar to that reported from North America. The frequency of the favorable response alleles varies considerably according to ethnicity, being more common in self‐reported Asians and Maori/Pacific Islanders than Caucasians, Aboriginals, and Mediterraneans.